IMPLEMENTASI MODERASI BERAGAMA DALAM PEMBENTUKAN KARAKTER SISWA DI SMPN 39 SAMARINDA - MUHAMMAD REDZA MADZKURI; Muchamad Eka Mahmud; Rahmatiana Azizatun Nisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Implementation of religious moderation in character building of students at SMPN 39 Samarinda and analysis of supporting and inhibiting factors. The study used a qualitative approach with a case study type, involving the principal, teachers, extracurricular instructors, and students as informants selected through purposive sampling technique. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of religious moderation at SMPN 39 Samarinda is carried out through the integration of moderation values ​​in learning, strengthening an inclusive school culture, and habituation through co-curricular and extracurricular activities. The values ​​of tolerance, fairness, dialogue, and cooperation across differences are the main focus in character building of students. Although it has a positive impact on increasing tolerance and harmony among students, the implementation of religious moderation still faces obstacles in the form of external influences, limitations of innovative learning models, and diverse student understanding. This study concludes that the practice of religious moderation in schools has proven effective in shaping moderate and inclusive student character, although it requires strengthened collaboration between schools, families, and the community for optimal and sustainable results.